Development in the acquisition of qualifying adjectives in the english language through a system of play-based learning activities for fifth graders in room a at Jaime Roldós Aguilera elementary school - Sánchez Lino, Sonia Noemí; Jumbo Calderon, Steffi Doménica (Machala: Universidad Técnica de Machala, 2023)
The aim of this research is to develop a system of play-based learning activities specifically designed for fifth grade students in room A. The study highlights the play-based learning method as a tool in the development of vocabulary acquisition, particularly in the understanding and use of qualifying adjectives in different contexts. The research uses a qualitative, non-experimental methodology of participatory action, so the theoretical framework is based on various definitions of the play-based learning method and its evolution over the years in education. The system of play-based learning activities included a series of games designed to promote the identification, use, and understanding of descriptive adjectives in everyday situations. These games were adapted to the needs of the student population, encouraging active participation and enjoyment in the learning process. The research results revealed significant progress in the acquisition of descriptive adjectives by the children who participated in the system of play-based learning activities and provide a strong foundation for future research on the role of play in English language acquisition, highlighting its potential to enhance vocabulary instruction.
El presente trabajo investigativo tiene como objetivo la elaboración de un sistema de actividades lúdicas orientado específicamente a los estudiantes de quinto año de educación básica paralelo A. El estudio resalta al método lúdico como una herramienta en el desarrollo de la adquisición de vocabulario y, en particular, para la comprensión y el uso de adjetivos calificativos en diversos contextos. La investigación cuenta con una metodología cualitativa no experimental de tipo acción participativa, por tal razón, el marco teórico se apoya en diversas definiciones del método lúdico y su evolución a lo largo de los años en la educación. El sistema de actividades lúdicas incluyó una serie de juegos diseñados para promover la identificación, el uso y la comprensión de adjetivos calificativos en situaciones cotidianas. Estos juegos se adaptaron a las necesidades que presentaban los estudiantes de la población, fomentando la participación activa y la diversión durante el proceso de aprendizaje. Los resultados de la investigación revelaron un progreso significativo en la adquisición de adjetivos calificativos por parte de los niños que participaron en el sistema de actividades lúdicas y proporciona una base sólida para futuras investigaciones sobre el papel del juego en la adquisición del idioma inglés, destacando su potencial para enriquecer la enseñanza de vocabulario.
Keywords: PLAY-BASED; LEARNING; ACTIVIT; ADJECTIV